Keeping computers from making mistakes: quis custodiet? (Economist, 1991)
Silvio Micali and Paul Feldman, mathematicians at the Massachusetts Institute of Technology, have developed a promising new technique for ensuring a foolproof error-correcting system within a computer. To enable computers to check each other's errors, the system takes a democratic approach whereby various parts of the system vote and the majority is considered correct. To address the trick of arranging the voting so that the majority cannot be deceived, Micali and Feldman use the notion of zero-knowledge proof. The idea entails having one component convince another that it possesses secret knowledge (fragments of mathematical proofs) without revealing that knowledge to some part that does not already have it.